Mechanical Behavior and Optimization of Graphene-Reinforced TPU/PDMS Composites for Biomedical Applications - Emad Zuhair Gheni; Adwaa Mohammed Abdulmajeed; Mujtaba A. Flayyih; Emad Kadum Njim (ASEAN Journal for Science and Engineering in Materials, 2027)
This study investigates the mechanical behavior and optimization of graphene-reinforced thermoplastic polyurethane (TPU) and polydimethylsiloxane (PDMS) composites for biomedical applications. A combined analytical, statistical, and computational approach was employed, including MATLAB modeling, regression analysis, and ANOVA. The results demonstrate that increasing PDMS content reduces elastic modulus, yield strength, and fatigue performance, while enhancing flexibility and impact resistance. The incorporation of nanographene significantly improves mechanical properties, with tensile strength exceeding 40 MPa and enhanced stiffness due to effective load transfer. Statistical analysis confirms that PDMS volume fraction is the dominant factor influencing performance. Optimal properties are achieved at 20–30% PDMS with graphene reinforcement, providing a balanced combination of strength, flexibility, and durability for biomedical applications.